Using Virtual Cities in Teaching Architecture and Urban Planning:: Auroville - RUSSELL, Peter; HEUER, Tom; STACHELHAUS, Thomas (ARCC Conference Repository, 2019)
The paper describes the Auroville project, which is in essence, the creation of a virtual and fictional city for use in architectural education. The project is firstly a didactical method for teaching fundamental Computer Aided Architectural Design (CAAD). Furthermore, by encouraging the design of infrastructure projects for the city, the students are initiated in cooperative work practices. Thirdly, as the virtual city has grown, the students have been confronted with urban planning issues such as conservation and renewal. Auroville is a fictive city based on the writings of the Guru Sri Aurobindo. The authors have mapped out the city using CAD software and essentially have created a palette of lots on which students can "build". The lots are assigned or acquired by each student at the beginning of the semester and in a series of exercises stretching over the semester, a built environment is created for these lots. The lot descriptions are connected to a central CAAD server so that a complete threedimensional city file structure is created. This allows the students to see the city as a whole as well as the urban effects of their designs (as well as those of their neighbour's.) In the past three years, approximately 900 students have taken part in the Auroville project. Indeed, the city, as originally laid out, is well nigh full. This led the organisers to focus work on infrastructure issues such as urban transit. Nonetheless, many students wish to continue work on individual parcels. This has also led to planning proposals by the students to "remove and replace" so called unsightly buildings. This has allowed urban planning issues to be raised. As well, the group has attempted to find ways to democratically resolve conflicting views. These resolutions are also used to plan larger scale infrastructure projects. A seminar dedicated to designing light rail transit lines and their stations focused on the balance between commonality and individuality. Auroville can be seen as a microcosm of current urban planning problems. The accelerated speed of development in the city serves the pedagogical role well. The negligible monetary costs in renewing the lots serve to highlight the other costs involved in real-world urban fragment issues such as cultural heritage, time and the image of the city. Current work is focused in three areas. Firstly, on a social engineering level, the authors are seeking to establish a "city council" in order to allow the students to autonomously direct the development of Auroville. Secondly, the technical conversion of the CAAD files into immersive VR files will allow real time exploration of the city. Lastly, the extension and structuring of the CAAD files could allow a wider range of analysis to take place. Additional functionality through and time-based simulation will allow technical issues such as solar gain, wind movement, traffic analysis, etc to be taught using the virtual city Auroville.